Gait characteristics in older women with osteoporosis and fear of falling. (September 2013) - Löfgren, Niklas; Halvarsson, Alexandra; Ståhle, Agneta; Franzén, Erika
Abstract: Ageing affects gait characteristics during walking under single- and dual-task conditions. Osteoporosis in elderly with fear of falling may further implicate gait alterations. The aims were to characterize spatiotemporal gait parameters, by comparing gait performance at comfortable speed to gait at maximal speed and while performing a dual task, respectively, and to investigate the relationship between gait characteristics and ageing in older women with osteoporosis and self-reported fear of falling. Seventy-nine elderly women (mean age 76 years, range 65–87), with osteoporosis and fear of falling, walked at comfortable and maximal speed and during a cognitive dual task, using the GAITRite ® walkway system. Subjects were divided into three age groups (65–69, 70–79, 80 + years). Divergences were analysed with analysis of variance. At maximal gait speed participants increased velocity, cadence, step length and swing phase, and reduced both double support and stance phase ( p < 0.001). Dual-task walking decreased cadence ( p < 0.001), increased step width ( p = 0.007) and step length variability ( p < 0.001). Gait performance, especially during a dual task diverged most in the oldest subjects, indicating that they are at a higher risk of falling. This study only found minute alterations compared with normative gait data in healthy elderly.